A Formal Model of text annotation based on XML entities - Geci, Branko (Array, 2005)
The paper proposed an annotation framework (annotation formalism) based on XML entities.analysis of the annotation proposed was made by means of a series of simulations that include XML and DTD test file generation, based on XML fragments and time measurements (durations of loading of test files into the XML parser).